2014
DOI: 10.1371/journal.pone.0085858
|View full text |Cite
|
Sign up to set email alerts
|

Independently Outgrowing Neurons and Geometry-Based Synapse Formation Produce Networks with Realistic Synaptic Connectivity

Abstract: Neuronal signal integration and information processing in cortical networks critically depend on the organization of synaptic connectivity. During development, neurons can form synaptic connections when their axonal and dendritic arborizations come within close proximity of each other. Although many signaling cues are thought to be involved in guiding neuronal extensions, the extent to which accidental appositions between axons and dendrites can already account for synaptic connectivity remains unclear. To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 74 publications
2
23
0
Order By: Relevance
“…These findings can shed light on the study of neural networks growth and development, because hubs could integrate information from the distant regions of neural network. The node distributions are similar to experimental [41,19,42] and theoretical distributions [43]. Scale-free networks (SFNs) have degree distributions with power-law tails P (k) ∼ k −γ .…”
Section: Discussionsupporting
confidence: 71%
“…These findings can shed light on the study of neural networks growth and development, because hubs could integrate information from the distant regions of neural network. The node distributions are similar to experimental [41,19,42] and theoretical distributions [43]. Scale-free networks (SFNs) have degree distributions with power-law tails P (k) ∼ k −γ .…”
Section: Discussionsupporting
confidence: 71%
“…It has been shown that when the leading process of neurons reach the marginal zone (MZ), intensive branching occurs, giving rise to complex dendritic arborization and synaptic connectivity (Chai et al 2014;van Ooyen et al 2014). However, in the Spag6-transfected neurons at P5, we noticed that the number of dendrites and their length were significantly decreased compared with those in the control (Fig.…”
Section: Overexpression Of Spag6 Reduced the Neurite Number And Lengthmentioning
confidence: 84%
“…Mammalian cortical development requires several subtle processes, including progenitor cell proliferation (InglisBroadgate et al 2005;Weimer et al 2009), neuronal migration (Frotscher et al 2009;Liu 2011), and establishment and refinement of synaptic connectivity (Chai et al 2014;van Ooyen et al 2014). Disturbance in any single step causes specific neurological disorders with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Neuron connectivity is provided by numerous axons whose density decrease approximately exponentially as a function of distance [23,24]. In modelling, the connectivity functions are usually considered to be symmetric, that is, axon connections between points x and y have the same density as between y and x.…”
Section: Discussionmentioning
confidence: 99%
“…Connectivity functions can be estimated from the data in [23,24]. It exponentially decreases with the rate of decrease in the interval 3-10 times at the at the distance 0.03 cm.…”
Section: Appendix 2 the Values Of Parametersmentioning
confidence: 99%